A Vocabulary for Numerical Control - Campbell, Clifton Paul. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
This glossary presents a standardized nomenclature for numerical control. It defines and describes some 286 technical words, terms, abbreviations, and acronyms which form a specialized vocabulary. The aim of this glossary is to provide a means for arriving at some common understanding of terminology for numerical control technology. Numerous entries in this glossary are used in metalworking, data processing, and other associated occupations. However, all the technical words, terms, abbreviations, and acronyms are defined and described as they apply to numerical control. A selected bibliography and an introduction which defines numerical control are also included. (HM)
ERIC Note: Contains light and broken type particularly in Bibliography.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Automation; Bibliographies; Computer Assisted Testing; Definitions; Equipment; Glossaries; Machinery Industry; Science Materials; Technology; Vocabulary; Reference Materials, Vocabularies/Classifications.